A Novel Enzymatic Process to Produce Oxalate Depleted Starch From Taro. (12th March 2018) - Kumar, Kunal; Belur, Prasanna D.
Abstract : A novel process comprising treatment of Taro ( Colocasia esculenta (L.) Schott) tuber flour with oxalate oxidase enzyme is developed to deplete the oxalate content. Oxalate oxidase enzyme produced by an endophyte, Ochrobactrum intermedium CL6 is employed to treat taro tuber flour. The treatment followed by extraction of starch results in a 97% reduction in total oxalate content. Further, several physicochemical properties such as paste clarity, swelling power, solubility, amylose content, granule size of starch produced out of enzyme treatment are studied and compared with properties of taro starch produced without enzyme treatment. The study reveals that enzyme treatment does not bring appreciable changes in the studied parameters. The taro starch produced by enzyme treatment shows very low paste clarity (9.38%), high swelling power (15.32 g/g), very low solubility (21.66%), and low amylose content (7.52%) at 100 °C compared to potato and sweet‐potato starches. X‐ray diffraction data reveal that taro starch possesses an A‐crystalline form, unlike the B‐crystalline form found in potato and sweet potato starch. To the best of the authors knowledge, for the first time, the use of oxalate oxidase to produce oxalate depleted taro starch is reported. One of the interesting food industry applications of oxalate‐depleted taro starch, among many other uses could be for baby food formulation because of its small granule size. Abstract : For the first time, oxalate oxidase is used in Taro tuber processing to reduce oxalate content. This novel process could eliminate 97% of total oxalate content in Taro starch. The physicochemical properties of starch remain unaltered after enzyme treatment.